Analyzing The Effect of Cylinder Liner Bronze Alloys on Hardness - Hasbullah, Ichsan; Pratama, Aditya Wahyu (METAL: Jurnal Sistem Mekanik dan Termal, 2024)
The quality of a component material is a significant issue in today's society, where the concept of "quality for a price" is a prevalent one. This phenomenon is observed across various sectors, including official manufacturers, local factories, and even students. The objective is to consider and implement measures to enhance the quality of components, aiming for a satisfactory value. The influence of the hardness value on the ductile iron alloy with AB2 is a key factor in this study. The aim is to identify the ideal mass percentage quantity to obtain a satisfactory hardness value. This is based on the understanding that the limited quantity of gray cast iron in cast furnaces affects the value of its mixture with AB2. The process from start to finish encompasses a number of stages, during which the incorporation of AB2 into ductile iron results in a change in the quality of the molten metal, which becomes visibly more liquid. In contrast, the impact of the aluminum element is relatively modest, although the final value of the alloy, which is 37% nickel, significantly increases the hardness value. This type of iron is widely used in automotive products. It is recommended that production parties, especially those involved in the manufacture of automotive components, consider the indications that occur in the values of this test. This is because the development of material improvements has been very rapid in recent times. The hardness value achieved by the non-alloy was recorded at 372.92 HVN, the 14% AB2 alloy was 509.94 HVN, the 25% AB2 alloy had a value of 408.79, and the 37% AB2 alloy exhibited a twofold increase from the value without the alloy, namely 679.96 HVN.